PENJADWALAN PRODUKSI PADA SISTEM MANUFAKTUR REPETITIVE MAKE TO ORDER FLOW SHOP MELALUI PENDEKATAN THEORY OF CONSTRAINTS - Sodikin, Imam; Mashuri, Aang (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
PT. Jaya Pulau Bintan, Bangka is a company that produces rubber in the form of semi-finished materials. Companies experiencing difficulties in meeting consumer demand is continuous, because the rubber product manufacturing process is very complicated and time consuming. The research method used in addressing the problems the company is the method of scheduling a flow shop with the approach of theory of constraint in repetitive manufacturing systems make to order. The result of data processing by using 2 production scheduling system, namely FCFS scheduling with makespan yield of 18.96 days. While the TOC scheduling with makespan obtained by 16.02 days in order to obtain savings of 2.94 days. Scheduling production with the TOC proposed because it has a greater throughput and successfully utilize the resources constraints, especially at work stations more effectively and efficiently.